Case Report: Primary small bowel adenocarcinoma with peritoneal metastasis responded well to a CapeOX + bevacizumab regimen - Fu, Guang; Tang, Zhen; Xu, Zishun; Zhang, Shao (Frontiers in Gastroenterology, 2023)
Small bowel adenocarcinoma (SBA) is a rare condition often presenting with various nonspecific gastrointestinal symptoms, making its diagnosis challenging. Delayed diagnosis is common, as patients may not receive the correct diagnosis until complications arise, necessitating further investigations. Furthermore, the management of SBA patients poses difficulties due to the scarcity of high-quality evidence.In this report, we present the case of an elderly man with SBA in the ileum who arrived at our emergency room with acute abdomen. The diagnosis was not made until the SBA caused a perforation, leading to severe abdominal pain. An emergent exploratory laparotomy revealed a 3*3cm perforated tumor in the ileum, along with widespread metastatic nodules on the omentum, ascending colon, descending colon, and rectum. Postoperative pathological evaluation confirmed the diagnosis of SBA with peritoneal metastasis (pT4N2M1, stage IV). Following surgery, the patient received palliative systemic chemotherapy, which included the CapeOX regimen along with the anti-VEGF monoclonal antibody Bevacizumab. Remarkably, the patient responded well to this therapy, displaying good tolerance, and showed no signs of disease progression. As of now, the patient remains in good health and is continuing with regular follow-up.Early diagnosis of small bowel adenocarcinoma remains a challenge. Delayed diagnosis can lead to a poor prognosis, underscoring the importance of considering SBA as a potential diagnosis in patients with unexplained abdominal pain and gastrointestinal symptoms. This case also highlights the efficacy of palliative chemotherapy with the CapeOX regimen plus Bevacizumab in controlling SBA..